2018
DOI: 10.3390/ijerph15122891
|View full text |Cite
|
Sign up to set email alerts
|

Household Air Pollution, Levels of Micronutrients and Heavy Metals in Cord and Maternal Blood, and Pregnancy Outcomes

Abstract: Cooking with kerosene emits toxic pollutants that may impact pregnancy outcomes. Sixty-eight women in their first trimester of pregnancy, kerosene users (n = 42) and liquefied natural gas (LNG) users (n = 26), were followed until birth. Maternal and cord blood were collected immediately after birth. Levels of micronutrients and heavy metals were quantified. Pregnancy outcomes (gestation age (GA), birth weight (BW), and chest and head circumference) were also measured. Mean (± standard deviation (SD)) age of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…To date, no studies were found that associate ambient air pollution during pregnancy with either urinary or placental iodine concentrations. However, in line with our observations, a recent study about household air pollution in pregnant Nigerian women found that cord blood levels of iodine, and other essential elements, were lower in women who cooked with kerosene compared to those who cooked with liquefied natural gas ( Arinola et al, 2018 ). Furthermore, our findings are consistent with those of Ghassabian and colleagues, who investigated five cohorts, located in Europe and the United States ( Ghassabian et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…To date, no studies were found that associate ambient air pollution during pregnancy with either urinary or placental iodine concentrations. However, in line with our observations, a recent study about household air pollution in pregnant Nigerian women found that cord blood levels of iodine, and other essential elements, were lower in women who cooked with kerosene compared to those who cooked with liquefied natural gas ( Arinola et al, 2018 ). Furthermore, our findings are consistent with those of Ghassabian and colleagues, who investigated five cohorts, located in Europe and the United States ( Ghassabian et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a possible association between spontaneous abortions and premature birth and air pollutants has been reported [ 21 ]. Whether SO 2 acts via direct means or indirectly via impacts on micronutrients or heavy metals is less clear [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a possible association between spontaneous abortions and premature birth and air pollutants has been reported [21]. Whether SO 2 acts via direct means or indirectly via impacts on micronutrients or heavy metals is less clear [22]. All 3 pollutants were associated with postneonatal mortality, albeit with different patterns of association at different levels of exposure, with PM 10 associated with postneonatal mortality even at low exposure, SO 2 at intermediate and high exposure, and NO 2 only at the highest exposure.…”
Section: Plos Medicinementioning
confidence: 99%
“…Even though none of the studies reviewed explored household air pollution, there is evidence that it also contributes to poor pregnancy outcomes, especially in developing countries where cooking is done by burning of biomass in poorly ventilated homes (12,(48)(49)(50). A number of measures can be taken to improve air quality and reduce the negative impacts of air pollution on overall health and on gestational health in particular.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that exposure to air pollution adversely affects human health (4)(5)(6)(7)(8). Additionally, in the last two decades, evidence has emerged that exposure to a variety of pollutants in the air and other environmental factors increase the risk of adverse pregnancy outcomes (9)(10)(11)(12). Further, evidence is accumulating that adverse outcomes such as low birth weight (LBW), preterm birth (PTB) and small for gestational age (SGA) are common in racial minority groups (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%